2020
DOI: 10.1108/jfc-07-2020-0133
|View full text |Cite
|
Sign up to set email alerts
|

Tax evasion, political/public corruption and increased taxation: evidence from Zimbabwe

Abstract: Purpose The purpose of this paper is to examine the relationship between tax evasion, political/public corruption and increased taxation in Zimbabwe’s small and medium-sized enterprises (SMEs). Design/methodology/approach The study as a descriptive survey used questionnaires and interviews as research instruments for collecting data. Findings The findings revealed that most SMEs are no longer paying some form of taxes as expected since the Government of Zimbabwe through the Ministry of Finance and Reserve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…As expected, higher tariffs motivate fraudulent activities of evading, paying custom duties, excise duty and other forms of trade taxes. A recent study from Kurauone et al (2020) find that increase in tax rates by the tax authorities or the government encourages tax evasion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected, higher tariffs motivate fraudulent activities of evading, paying custom duties, excise duty and other forms of trade taxes. A recent study from Kurauone et al (2020) find that increase in tax rates by the tax authorities or the government encourages tax evasion.…”
Section: Resultsmentioning
confidence: 99%
“…Relating to equation (6) and previous literature discussed above, we assume that, to prevent the criminal and fraudulent activities that can be used in various sectors of the economy especially in revenue collection, good governance, transparency, credibility and the monitoring of political and public officials including the tax officials is subsequently expected to follow. This can be achieved in stages particularly in a country with developed legal infrastructure, strong monitoring and regulatory mechanisms (Kimbro, 2002; Kurauone et al , 2020). Additionally, Javorcik and Narciso (2017) argue that exporters from well-governed countries are reluctant to make false transactions and produce fake business documents.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Zimbabwe, liquidity crisis resulted from a combination of many factors and events such as highinterest rates in 1998, suspension of aid to the country by the IMF and the World Bank, land seizure in 2000, the drought in 2001, the Commonwealth suspension of Zimbabwe in 2002, and hyperinflation in 2006 (Khumalo 2017). In addition to these factors, Kurauone et al (2020) also mentioned corruption, and lack of transparency and accountability as causal factors. Further, the country has been under sanctions from the US for a long time now.…”
Section: Discussionmentioning
confidence: 99%
“…The currency was backed by the government's ability to pay back the debt to Afrexim Bank. Upon its introduction, the government indicated that the surrogate currency would be backed by a US$200 million support facility provided by the Cairo-based Afrexim Bank (Kurauone et al 2020). The surrogate currency was also described by Kuyedzwa (2019) as a false legal currency and a financial instrument used for local transactions only.…”
Section: The Surrogate Currency In Zimbabwementioning
confidence: 99%